Juridical Analysis Related to Freeze Contract Clause in E-Sport Career Employment Agreement in Indonesia - Harun Setiawan Hatibie; Weny Almoravid Dungga; Nurul Fazri Elfikri (Yayasan Cerdas Pedia Indonesia, 2026)
The e-sports industry in Indonesia is fostering professional relationships between athletes and team management through work agreements. However, the lack of specific legal frameworks has led to concerning contractual clauses, notably the freeze contract clause, which allows team management to indefinitely suspend an athlete's contract while preventing them from pursuing professional opportunities. This study examines the implications of such clauses on athletes' rights and welfare, utilizing normative legal research with legislative and conceptual methodologies. The findings indicate that while the freeze contract is rooted in the freedom of contract principle, it often lacks good faith and balance, resulting in potential bargaining inequalities, loss of wages, and career sustainability issues for athletes. Consequently, there is a pressing need for more precise regulations and contractual guidelines from e-sports institutions to enhance legal protection and equitable welfare for athletes.